2018
DOI: 10.1097/md.0000000000013752
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of proliferating cell nuclear antigen expression in colorectal cancer

Abstract: Background:A number of studies have attempted to determine the prognostic significance of proliferating cell nuclear antigen (PCNA) in patients with colorectal cancer (CRC), but the reports are controversial and inconsistent. Thus, we conducted a meta-analysis to clarify the value of PCNA in CRC prognosis.Methods:A systematic search of relevant studies was performed in 4 electronic databases including PubMed, Cochrane Library, Embase, and Web of Science until February 2018. Hazard ratios (HRs) combined with 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Furthermore, the expression level of PCNA was found to be related to clinicopathological features and prognosis of EC patients (Hareyama, 1994). Additionally, many studies have demonstrated that it is a poor survival biomarker in osteosarcoma, gastric, and colorectal cancer (Wang et al, 2017; Yin et al, 2017; Zhou et al, 2018). BIRC5 which encodes for survivin protein, is a member of inhibitor of apoptosis gene family and regulates apoptosis, while cell cycle studies suggest that BIRC5 is overexpressed both in EC and in EC cell lines (Pallares et al, 2005; Nabilsi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the expression level of PCNA was found to be related to clinicopathological features and prognosis of EC patients (Hareyama, 1994). Additionally, many studies have demonstrated that it is a poor survival biomarker in osteosarcoma, gastric, and colorectal cancer (Wang et al, 2017; Yin et al, 2017; Zhou et al, 2018). BIRC5 which encodes for survivin protein, is a member of inhibitor of apoptosis gene family and regulates apoptosis, while cell cycle studies suggest that BIRC5 is overexpressed both in EC and in EC cell lines (Pallares et al, 2005; Nabilsi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, epigenetic alterations can also influence clinical outcome of CRC patients. Hypermethylation in MLH1 or MGMT predicts good prognosis, whereas hypermethylation in p16 or hypomethylation in the promoters of LINE-1 and IGF-2 are related to poor prognosis [19,113,189,190,191].…”
Section: Clinical Relevance Of Molecular Alterations In the Serratmentioning
confidence: 99%
“…PCNA has been identified as a proliferating cell nuclear antigen that can serve a role in DNA replication and repair (21). Furthermore, previous studies have identified PCNA as a cell growth marker and a predictive indicator of various types of cancer, including colorectal cancer, gastric carcinoma and parotid gland cancer (22)(23)(24). In addition, it has been reported that upregulated PCNA is associated with poor survival in patients with esophagus squamous cell cancer (25), which is consistent with the results from our previous study on ESCA.…”
Section: Discussionmentioning
confidence: 99%